Role of epstein-barr virus in the severity of recurrent respiratory papillomatosis - Costa, Victor [UNESP]; El-Achkar, Vivian Narana [UNESP]; de Barros, Patrícia Pimentel [UNESP]; León, Jorge Esquiche; Ribeiro-Silva, Alfredo; Carlos, Román; Pignatari, Shirley Shizue Nagata; Ferreira, Silvaneide; Mello, Barbara Pereira; Sichero, Laura; Villa, Luisa Lina; Kaminagakura, Estela [UNESP] (Wiley, 2019)
Objective: The objective was to investigate the prevalence of the Epstein-Barr virus (EBV) and its association with human papilloma virus (HPV) detection, clinicopathological features, and the severity of recurrent respiratory papillomatosis (RRP). Methods: Cases of juvenile recurrent respiratory papillomatosis (JRRP) (n = 36) and adult recurrent respiratory papillomatosis (ARRP) (n = 44) were collected retrospectively and subdivided into low- and high-risk severity groups based on the Derkay score. We performed HPV detection and genotyping using a reverse hybridization protocol and investigated the presence of EBV by polymerase chain reaction (PCR) and in situ hybridization. CD21 levels were accessed by immunohistochemistry. Results: All samples were HPV-positive, including 49 cases of HPV 6, 26 cases of HPV 11, four cases of HPV 6 and 11 coinfections, and one case of HPV 16. EBV-DNA was detected in nine samples by PCR, although none of the cases were positive by means of in situ hybridization. CD21 immunoexpression was not statistically associated with any of the variables analyzed. HPV 6 detection was significantly higher in ARRP cases (P = 0.03), whereas HPV 11 was more prevalent in JRRP cases (P = 0.02) and was even more prevalent in JRRP cases of greater severity (Derkay laryngoscopic scale ≥20) (P = 0.04). Conclusion: The presence of EBV does not seem to play an important role in the progression/severity of RRP. Level of Evidence: 4 Laryngoscope, 2019.
Keywords: CD21; Epstein-Barr virus; human papilloma virus; severity; Squamous papillomatosis